(untitled) (Revista de História da UEG (REVHIST), 2020)
The text presents the trajectory of the documental estate of the photographer Mario Baldi (1896-1957), divided between Austria and Brazil, and the bilateral efforts to bring together the information needed to supplement both collections. We expose some basic data about the work of the photographer, along with the ways through which his production was brought to the public, both during his life and posthumously. Finally, we emphasize the passage from a collection split into two incommunicable halves, to a proposal of shared responsibility. Keywords: Photography. Museums. Mario Baldi.